Multi-organic dyes-immobilised zincite decorated silica-titania nanocomposite: A study on atomic site structural changes for pH sensor activity progression. (May 2022) - Alshoaibi, Adil; Islam, Shumaila
Highlights: Dyes immobilized zincite decorated silica-titania is synthesized by sol-gel method. Crack-free surface morphology is observed. Thermal stability at high temperatures (560 °C) is reported. The sensitivity is estimated 15.67 counts/pH with R 2 ∼ 0.99. High pKa ∼ 8 and rapid time response 0.13 s at pH 12 is observed. Abstract: Zinc oxide (zincite) decorated silica-titania nanocomposite (ZST-NC) is synthesized by sol-gel method. For dynamic pH range and fast-response fibre-optic pH sensing characteristics, a blend of phenol red, bromophenol blue, phenolphthalein, and cresol red is immobilised in ZST-NC (D/ZST-NC). A fundamental analysis revealed that ZST-NC and D/ZST-NC had crack-free morphology and thermal stability at 560 °C. The ZST-NC exhibited a surface roughness (Ra) 0.4 nm, a crystallite size 5 nm, and a refractive index 1.48. The D/ZST-NC revealed a Ra 0.8 nm, a crystallite size 2 nm, and a refractive index 1.49. The sensitivity of the D/ZST-NC coated optic fibre is estimated to be 15.67 counts/pH at 440 nm, with a determination coefficient (R 2 ) ∼99%. A high pKa ∼8 and a rapid response time 0.13 s at pH 12 are observed. The prepared pH sensor displays a reversible and non-leaching behaviour, which is advantageous for applied opto-chemical pH sensing purposes. Graphical abstract: Image, graphical abstract